Profile of Richard Robson, Susumu Kitagawa, and Omar M. Yaghi: 2025 Nobel laureates in Chemistry - Laura Gagliardi (Proceedings of the National Academy of Sciences, 2026)
The 2025 Nobel Prize in Chemistry honors Richard Robson, Susumu Kitagawa, and Omar M. Yaghi for establishing metal-organic frameworks (MOFs) as a new class of crystalline porous materials and, more broadly, for transforming how chemists design extended matter. Their work showed that solids could be built from well-defined inorganic and organic components with unusual control over structure, porosity, and function. This profile highlights the distinct and complementary contributions of the three laureates, from the conceptual foundations of network design to the demonstration of permanent porosity and the development of reticular chemistry. It also examines the broader scientific legacy of MOFs, including their impact on catalysis, separations, sustainability, and modern data-driven materials discovery.